Integrating genome-wide and epigenome-wide associations for antipsychotic induced extrapyramidal side effects - Kai Yao; Johan H. Thygesen; Siobhan K. Lock; Antonio F. Pardiñas; Antonia L. Pritchard; Israa Elbashir; Abdullah Lodhi; Zain-Ul-Abideen Ahmad; Michael C. O’Donovan; Michael J. Owen; James T. R. Walters; David St Clair; et al. (Psychopharmacology, 2026)
Rationale Antipsychotic medications are the first-line treatment for schizophrenia. Around 40% of people who are treated with antipsychotics could develop extrapyramidal side-effects (EPSE) including: (1) Dyskinesia, (2) Parkinsonism, (3) Akathisia, and (4) Dystonia. Objectives This study aimed to identify genetic risk factors for EPSE presence following antipsychotic treatment. Methods We conducted Genome-wide association (GWAS) and Epigenome-wide association (EWAS) meta-analyses of EPSE, with subset analyses separating first and second generation antipsychotic (FGA/SGA) exposure. We integrated significant EWAS findings from a between-case design to a comparable GWAS for association enrichment. We investigated whether polygenic risk scores (PRS) for schizophrenia, Parkinson’s disease, and Lewy-body dementia could predict EPSE. Results The primary GWAS top SNP rs2709733 (A/G) ( p = 5.755 × 10 −07 ) mapped to a long intergenic non-protein coding RNA, LINC01162 with consistent effects across all cohorts. Subset analyses with distinct FGA exposure indicated suggestive genes such as NAV2 , NRG3 , LSAMP and SGA exposure indicated SHISA9 and CNBD1 which are relevant for schizophrenia, autism, and epilepsy. In our primary EWAS, the most significant differentially methylated position (DMP) was cg05599348 (3.181 × 10 −07 ), located at chrX:103,174,718 (hg19) mapping to TMSB15B . Comparing EPSE cases to healthy controls, we identified nine DMPs associated with EPSE. The DMP cg12044923 (chr2:241453995, hg19), located within the STK32B gene, showed significant enrichment for EPSE association (permutation p = 0.010). STK32B is relevant to both psychiatric and movement disorders, suggesting potential shared mechanisms. Conclusions Our study sheds new light on the potential biological mechanisms underlying EPSE development in schizophrenia, highlighting the importance of exploring both methylation changes and SNP associations.

Longitudinal Impacts of Forest Loss on Bartonella and Hemotropic Mycoplasma Dynamics in Vampire Bats Within a Fragmented Habitat - Lauren R. Lock; Kristin E. Dyer; Dmitriy V. Volokhov; Anni Yang; M. Brock Fenton; Nancy B. Simmons; Daniel J. Becker (Molecular Ecology, 2026)
Habitat fragmentation can negatively impact wildlife, including increasing infectious disease risk. We assessed spatiotemporal changes in pathogen dynamics in vampire bats ( Desmodus rotundus ) in response to habitat fragmentation using general linear mixed models to investigate the influence of site, year, and tree cover on Bartonella spp. and hemotropic Mycoplasma spp. (hemoplasmas) infection risk in bats in one large and one small forest fragment in Belize across seven years. While Bartonella infections were more likely in the final years of the study regardless of site, hemoplasma infection likelihood was not significantly different across years or sites. Bartonella infections were associated with increased forest loss in the large fragment only, whereas hemoplasma infections were not associated with forest loss. The effects of site, year, and forest loss on infection likelihood varied by pathogen genotype despite low model explanatory power. Neither site nor year was associated with bartonellae, but one genotype was positively associated with tree cover. Two hemoplasmas were influenced by year with differing trends: one genotype was negatively associated with tree loss across sites, while another was positively associated with forest loss at the small fragment only. Both pathogens were similarly influenced by bat demographics and showed instances of infection status and genotype switching. Our work suggests that the effects of habitat fragmentation on infection risk depend on both the pathogen and specific genotype, complicating expectations of how environmental change affects wildlife disease dynamics. Efforts to mitigate infectious disease impacts in fragmented systems should be tailored to specific pathogens of concern.

Nuclear and organellar phylogenies provide insights into evolutionary history and species boundaries in Galdieria - Manuela Iovinella; Sarah C.L. Lock; Luke C.M. Mackinder; James P.J. Chong; Georg A. Feichtinger; Sally James; Daniel Jeffares; Antonino Pollio; Emanuele Del Guacchio; Hwan Su Yoon; Claudia Ciniglia; Seth J. Davis (Algal Research, 2026)

Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

Symbiodiniaceae phenotypic traits as bioindicators of acclimatization after coral transplantation - Colin J. Anthony; Colin Lock; Gonzalo Pérez-Rosales; Héloïse Rouzé; Loreto Paulino; Laurie J. Raymundo; Bastian Bentlage (Marine Pollution Bulletin, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Scalable mesoporous biochars from bagasse waste for Cu (II) removal: Process optimisation, kinetics and techno-economic analysis - Julius G. Bongosia; Amthal Al-Gailani; Ben W. Kolosz; Adrian Loy Chun Minh; Serene Sow Mun Lock; Kin Wai Cheah; Martin J. Taylor (Journal of Environmental Management, 2024)

Green pathways for biomass transformation: A holistic evaluation of deep eutectic solvents (DESs) through life cycle and techno-economic assessment - Chung Loong Yiin; Zhi Ying Lai; Bridgid Lai Fui Chin; Serene Sow Mun Lock; Kin Wai Cheah; Martin J. Taylor; Amthal Al-Gailani; Ben W. Kolosz; Yi Herng Chan (Journal of Cleaner Production, 2024)

Blue mussel (Mytilus edulis) silage, a possible low trophic marine protein source for Atlantic salmon (Salmo salar L.) - Sahar Sartipiyarahmadi; Antony J. Prabhu Philip; Aksel N. Forshei; Harald Sveier; Silje Steinsund; Malin Kleppe; Erik-Jan Lock; Angelico Madaro; Tom Johnny Hansen; Øivind Strand; Martin Wiech; Jan Vidar Jakobsen; et al. (Aquaculture, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Depth‐independent phenotypic variation of massive Porites coral color morphs - Colin J. Anthony; Grace McDermott; Colin Lock; Therese Miller; Bastian Bentlage; Laurie J. Raymundo (Marine Ecology, 2024)
As coral reefs continue to decline due to anthropogenic stressors, community characterizations will reveal both historical selection processes and adaptive potential to environmental change. To address the potential role of color in the distribution and resilience of massive Porites corals, we surveyed the distributions of two dominant color morphs (brown and purple), and a unique intermediate state, across a depth gradient in Guam, Micronesia. We found that brown colonies dominated populations across all depths, and larger colonies had higher rates of partial tissue mortality and active disease lesions. Despite the dominance of brown colonies, both brown and purple color morphs showed a high similarity in susceptibility, as indicated by the colony sizes, the severity of partial tissue mortality, and the prevalence of active disease lesions. This is a non‐intuitive result given the presence of phenotypic plasticity between color morphs, evident by an intermediate, transitionary stage between brown and purple colonies that suggests a functional divergence between one color over the other. The study also revealed the dominance of small colonies at depth, which provides some insight into the ecological impacts that may have shaped Guam's current massive Porites population size structure over the past several decades. With this, we provide foundational insight into the adaptive strategies and historical pressures that have shaped the modern massive Porites population.

Detection of human adenovirus F41 in wastewater and its relationship to clinical cases of acute hepatitis of unknown aetiology - Marina I. Reyne; Danielle M. Allen; Ashley Levickas; Pearce Allingham; Jonathan Lock; Arthur Fitzgerald; Cormac McSparron; Behnam F. Nejad; Jennifer McKinley; Andrew Lee; Stephen H. Bell; Joshua Quick; et al. (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Isolation and characterization of bacteriophage NTR1 infectious for Nocardia transvalensis and other Nocardia species - Stephanie Taylor; Teagan L. Brown; Joseph Tucci; Peter Lock; Robert J. Seviour; Steve Petrovski (Virus Genes, 2019)

Drought timing, not previous drought exposure, determines sensitivity of two shortgrass species to water stress - Nathan P. Lemoine; Robert J. Griffin-Nolan; Abigail D. Lock; Alan K. Knapp (Oecologia, 2018)

Hemodynamic Effects of Lipid-Based Oxygen Microbubbles via Rapid Intravenous Injection in Rodents - Katherine J. Black; Andrew T. Lock; Lindsay M. Thomson; Alexis R. Cole; Xiaoqi Tang; Brian D. Polizzotti; John N. Kheir (Pharmaceutical Research, 2017)

Amino acid composition, protein content, and nitrogen-to-protein conversion factors of 21 seaweed species from Norwegian waters - I. Biancarosa; M. Espe; C. G. Bruckner; S. Heesch; N. Liland; R. Waagbø; B. Torstensen; E. J. Lock (Journal of Applied Phycology, 2017)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

Edward Armitage Robinson 1921 – 2013 - J. M. Lock (Kew Bulletin, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Maladaptation and phenotypic mismatch in hatchery‐reared Atlantic salmon Salmo salar released in the wild - R. Stringwell; A. Lock; C. J. Stutchbury; E. Baggett; J. Taylor; P. J. Gough; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
Changes in body shape, fluctuating asymmetry ( FA ) and crypsis were compared among Atlantic salmon Salmo salar fry kept as controls in captivity and those released and subsequently recaptured in the wild according to a before‐after‐control‐impact ( BACI ) design. Hatchery fish that survived in the wild became more cryptic and displayed a much lower incidence of fin erosion and of asymmetric individuals than control fish kept in captivity. Significant differences in body shape were also apparent, and survivors had longer heads, thicker caudal peduncles and a more streamlined body shape than hatchery controls as early as 20 days following stocking, most likely as a result of phenotypic plasticity and non‐random, selective mortality of maladapted phenotypes. Hatchery‐reared fish typically perform poorly in the wild and the results of this study indicate that this may be due to phenotypic mismatch, i.e. because hatcheries generate fish that are phenotypically mismatched to the natural environment.

Coupling between subtropical cloud feedback and the local hydrological cycle in a climate model - Mark. J. Webb; Adrian P. Lock (Climate Dynamics, 2013)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Dietary fatty acids and inflammation in the vertebral column of Atlantic salmon, Salmo salar L., smolts: a possible link to spinal deformities - L Gil Martens; E J Lock; P G Fjelldal; A Wargelius; P Araujo; B E Torstensen; P E Witten; T Hansen; R Waagbø; R Ørnsrud (Journal of Fish Diseases, 2010)
Vegetable oils (Vo) are an alternative to fish oil (Fo) in aquaculture feeds. This study aimed to evaluate the effect of dietary soybean oil (Vo diet), rich in linoleic acid, and of dietary fish oil (Fo diet) on the development of spinal deformities under bacterial lipopolysaccharide (LPS)‐induced chronic inflammation conditions in Atlantic salmon, Salmo salar L. Fish [25 g body weight (BW)] were fed the experimental diets for 99 days. On day 47 of feeding (40 g BW), fish were subjected to four experimental regimes: (i) intramuscular injections with LPS, (ii) sham‐injected phosphate‐buffered saline (PBS), (iii) intraperitoneally injected commercial oil adjuvant vaccine, or (iv) no treatment. The fish continued under a common feeding regime in sea water for 165 more days. Body weight was temporarily higher in the Vo group than in the Fo group prior to immunization and was also affected by the type of immunization. At the end of the trial, no differences were seen between the dietary groups. The overall prevalence of spinal deformities was approximately 14% at the end of the experiment. The Vo diet affected vertebral shape but did not induce spinal deformities. In groups injected with LPS and PBS, spinal deformities ranged between 21% and 38%, diet independent. Deformed vertebrae were located at or in proximity to the injection point. Assessment of inflammatory markers revealed high levels of plasma prostaglandin E 2 (PGE 2 ) in the Vo‐fed and LPS‐injected groups, suggesting an inflammatory response to LPS. Cyclooxigenase 2 (COX‐2) mRNA expression in bone was higher in fish fed Fo compared to Vo‐fed fish. Gene expression of immunoglobulin M (IgM) was up‐regulated in bone of all LPS‐injected groups irrespective of dietary oil. In conclusion, the study suggests that Vo is not a risk factor for the development of inflammation‐related spinal deformities. At the same time, we found evidence that localized injection‐related processes could trigger the development of vertebral body malformations.

Spatial representation of overlearned arbitrary visuomotor associations - Meike J. Grol; Ivan Toni; Mireille Lock; Frans A. J. Verstraten (Experimental Brain Research, 2009)

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Distribution of corticotectal cells in macaque - T. M. Lock; J. S. Baizer; D. B. Bender (Experimental Brain Research, 2003)

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America - A. J. P. Smolders; R. A. C. Lock; G. Van der Velde; R. I. Medina Hoyos; J. G. M. Roelofs (Archives of Environmental Contamination and Toxicology, 2003)

Effects of stream size on bird community structure in coastal temperate forests of the Pacific Northwest, U.S.A. - Patricia A. Lock; Robert J. Naiman (Journal of Biogeography, 1998)
Vegetation and spring breeding bird populations associated with riparian forests on high and low order rivers of the Olympic peninsula, Washington (USA), were censussed in 1990 and 1991. The objectives were to (1) provide a baseline description of bird communities associated with unmanaged riparian forests, (2) determine whether there is a difference between bird communities along large and small rivers, and (3) identify what biophysical aspects of the fluvial corridor are most important in determining bird community structure. The approach was to link riparian bird community structure to river order and discuss relationships to vegetation, geomorphology and associated hydrologic disturbance regimes. Large rivers tended to have more deciduous vegetation than small rivers (P = 0.07) . Deciduous vegetation and patch types appeared to be linked to river size through stream valley shape and disturbance history. Bird species richness and abundance were significantly higher (P on larger rivers (67–140 m width) than on small rivers (12–21 m width) and were positively correlated with the percentage of deciduous trees present at a site. The data suggest that migrant birds, such as the black‐throated grey warbler (Dendroica nigrescens) and warbling vireo (Vireo gilvus) , require large tracts of contiguous hardwoods for successful breeding. Additionally, birds such as the Hammond's flycatcher (Empidonax hammondii) and hairy woodpecker (Picoides villosus) appear to depend on the juxtaposition of hardwoods and conifers during the breeding season. We conclude that bird communities on large rivers differ from those on small rivers and that these differences occur predictably with stream order.

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat - M. P. Chamberlain; E. A. Lock; B. A. Gaskell; C. J. Reed (Archives of Toxicology, 1998)

l -2-Chloropropionic acid metabolism and disposition in male rats: relevance to cerebellar injury - Ian Wyatt; Michael Farnworth; Andrew J. Gyte; Edward A. Lock (Archives of Toxicology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Olfactory toxicity of methyl iodide in the rat - C. J. Reed; B. A. Gaskell; K. K. Banger; E. A. Lock (Archives of Toxicology, 1995)

Immunohistochemical localisation of six glutathione S-transferases within the nasal cavity of the rat - Kulwinder K. Banger; John R. Foster; Edward A. Lock; Celia J. Reed (Archives of Toxicology, 1994)

Effects of water-borne cadmium on the skin of the common carp (Cyprinus carpio) - Y. Iger; R. A. C. Lock; J. C. A. van der Meij; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1994)

Calmodulin-mediated cadmium inhibition of phosphodiesterase activity, in vitro - Gert Flik; Jan G. J. van de Winkel; Peter Pärt; Sjoerd E. Wendelaar Bonga; Robert A. C. Lock (Archives of Toxicology, 1987)

Sexuality in mucorales - J. D. Bu'Lock; B. E. Jones; S. A. Quarrie; D. J. Winstanley (Archives of Microbiology, 1974)